2007
DOI: 10.1200/jco.2007.25.18_suppl.7651
|View full text |Cite
|
Sign up to set email alerts
|

Association between different potential predictive markers from TRUST, a trial of erlotinib in non-small cell lung cancer (NSCLC)

Abstract: 7651 Background: Recent studies have examined potential predictive markers in NSCLC patients (pts) treated with EGFR tyrosine kinase inhibitors. However, few data are available on inter-relationships between different markers. Clinical and molecular markers were analyzed for patients from TRUST, an open label, non-randomized trial initiated to provide erlotinib access to pts with advanced NSCLC. Methods: 393 German pts (99% Caucasian) with stage IIIb/IV NSCLC were included. Markers/characteristics assessed we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…After EGFR-TKIs were approved for advanced NSCLC, the OS of advanced NSCLC patients increased [9] . In the BR.21 [12] and TRUST [13] studies, erlotinib monotherapy had better efficacy and was safer in second-line or third-line treatment than placebo. Recently, the Tailor study indicated that patients with wild-type EGFR who underwent previous treatment did not obtain a PFS benefit from second-line erlotinib compared with docetaxel [14] .…”
Section: Discussionmentioning
confidence: 98%
“…After EGFR-TKIs were approved for advanced NSCLC, the OS of advanced NSCLC patients increased [9] . In the BR.21 [12] and TRUST [13] studies, erlotinib monotherapy had better efficacy and was safer in second-line or third-line treatment than placebo. Recently, the Tailor study indicated that patients with wild-type EGFR who underwent previous treatment did not obtain a PFS benefit from second-line erlotinib compared with docetaxel [14] .…”
Section: Discussionmentioning
confidence: 98%